Metaphorical thinking as a means of semantic content of the result of creativity - Lidiia Slipchyshyn (Vasyl Stefanyk Precarpathian National University, 2017)
The role of metaphors in creative thinking development is lightened, the cognitivepotential of metaphorical thinking and the importance of its use in the preparation of futureprofessionals for folk arts and crafts in vocational school is considered. Key words: creative thinking, metaphor, arts, folk arts and crafts specialist, vocationalschool.